PREDICTION OF PM2.5 WITH AEROSOL OPTICAL DEPTH (AOD) USING SON PHOTOMETER LEVEL 2.0 ON A DIFFERENT WAVELENGTH (STUDY: BANDUNG) - INDRAWATI, ASRI
Aerosol measuring observation has been done routinely since May 2009 in Bandung using CIMEL sun photometer integrated with a global aerosol monitoring network AERONET under the auspices NASA. Five years data analysis conducted from 2009 – 2013 on Aerosol Optical Depth (AOD) based on measurement obtained at seven wavelengths are 340 nm, 380nm, 440 nm, 500 nm, 675 nm, 870 nm, and 1020 nm, the average results for each wavelengths from 2009–2013 are 0.575; 0.530; 0.461; 0.404; 0.272; 0.195; and 0.153 respectively. The AOD value was analyzed further to look at temporal trend, both monthly and seasonal. Then, based on angstrom exponent calculation from the whole data, around 85% shows fine mode (?>1), this is in accordance with the aerosol size distribution based on bimodal distribution shows the fine mode domination compare to coarse mode. Data distribution in a scatter plot between AOD and Angstrom exponent values indicate the aerosol type in Kota Bandung is mixed aerosol. The correlation between AOD and turbidity coefficient give the linier comparison, the greater AOD value gives the greater value of atmosphere turbidity coefficient. The value of turbidity coefficient will affect in reduced visibility and air quality, this condition occurs in the dry season (JJA) and the dry-rainy transition season (SON). Estimated value of PM2.5 measurement and AOD creat equal value at any wavelength.